Effects of hyperoxia on dyspnoea and exercise endurance in fibrotic interstitial lung disease. Issue 5 (25th May 2017) - Schaeffer, Michele R.; Ryerson, Christopher J.; Ramsook, Andrew H.; Molgat-Seon, Yannick; Wilkie, Sabrina S.; Dhillon, Satvir S.; Mitchell, Reid A.; Sheel, A. William; Khalil, Nasreen; Camp, Pat G.; Guenette, Jordan A.
Dyspnoea is a major source of distress and is the hallmark symptom of patients with interstitial lung disease (ILD). Supplemental oxygen may alleviate dyspnoea by attenuating arterial oxygen desaturation, increasing oxygen delivery and reducing the drive to breathe; however, previous studies show conflicting results on the effectiveness of supplemental oxygen on dyspnoea and exercise performance in ILD [1–6]. Methodological factors in these studies likely led to underestimation of the potential magnitude of improvement, including an insufficient fraction of inspired oxygen ( F IO2 ) and/or the use of self-paced walking tests and incremental cycle tests rather than constant-load exercise protocols [3–8]. Dyspnoea was also either not evaluated or only evaluated at peak exercise [1, 3–6], which is insensitive to change compared to more clinically relevant submaximal exercise [8]. Finally, some studies were retrospective and did not include a blinded room-air exercise trial, making it difficult to rule out the potential placebo effect [4, 5]. The purpose of this study was to determine the effects of hyperoxia on exercise endurance as well as the intensity and qualitative dimensions of exertional dyspnoea in patients with fibrotic ILD. Hyperoxia significantly improves exertional dyspnoea and exercise tolerance in patients with fibrotic ILD http://ow.ly/WbHf309VwcM